Proszę jeszcze raz opomoc w rozwiązaniu krok po kroku BB: Rozwiąż nierówność
 2x+3 6 2 
przykład a


+3

 X−4 x−4 3 
 2 x 
przykład b


− 2 >0
 x+5 x+5 
19 maj 19:42
Szkolniak: ad a)
3(2x+3) 6*3 11(x−4) 


+

∧ x∊D=R\{4}
3(x−4) 3(x−4) 3(x−4) 
6x+9 11x−26 


3(x−4) 3(x−4) 
6x+9 11x−26 


≥0
3(x−4) 3(x−4) 
5(7−x) 

≥0 ⇔ 5(7−x)*3(x−4)≥0
3(x−4) 
15(x−7)(x−4)≤0 Odpowiedź: x∊(4;7>
19 maj 19:52
Mila: x≠4
2x+3 6 11 



x−4 x−4 3 
2x−3 11 


≥0
x−4 3 
3*(2x−3)−11(x−4) 

≥0
3*(x−4) 
−5x+35 

≥0⇔(−x+7)*(x−4)≥0
3*(x−4) 
x∊(4,7>
19 maj 20:46
Mila: b) x≠−5
2−x−2*(x+5) 

>0⇔
x+5 
2−x−2x−10 

>0
x+5 
 8 
(−3x−8)*(x+5)>0⇔−3*(x+

)*(x+5)>0 /: (−3)
 3 
 8 
(x+

)*(x+5)<0
 3 
 8 
−5<x<−

 3 
19 maj 20:53